1990
DOI: 10.1161/01.str.21.5.721
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intravenous naloxone for the treatment of acute ischemic stroke.

Abstract: To evaluate the safety and possible efficacy of high-dose naloxone for the treatment of acute cerebral ischemia, 38 patients received a loading dose of 160 mg/m 2 over 15 minutes followed by a 24-hour infusion at the rate of 80 mg/m 2 /hr. Nausea and/or vomiting were common side effects. Naloxone was discontinued in seven patients (because of hypotension in one, bradycardia and hypotension in two, myoclonus in one, focal seizures in two, and hypertension in one); all seven patients responded to treatment and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 48 publications
1
23
1
Order By: Relevance
“…546 Although a dose-escalation study of naloxone found the medication to be safe, no hint of efficacy was noted. 547 No benefit has been reported from treatment with the opioid antagonist nalmefene, as noted in other clinical trials. 548,549 The neuroprotective agent NXY-059 (Cerovive) has been tested in clinical trials in acute stroke.…”
Section: Neuroprotective Agentsmentioning
confidence: 96%
“…546 Although a dose-escalation study of naloxone found the medication to be safe, no hint of efficacy was noted. 547 No benefit has been reported from treatment with the opioid antagonist nalmefene, as noted in other clinical trials. 548,549 The neuroprotective agent NXY-059 (Cerovive) has been tested in clinical trials in acute stroke.…”
Section: Neuroprotective Agentsmentioning
confidence: 96%
“…764 Although a dose-escalation study of naloxone found the medication to be safe, no signal of efficacy was noted. 765 Similarly, no benefit was noted in trials of the opioid antagonist nalmefene. 472,766 Free radicals produced during cerebral ischemia are well-known mediators of neuronal injury.…”
Section: Pharmacological Agentsmentioning
confidence: 99%
“…[1][2][3] The National Institutes of Health (NIH) Stroke Scale is probably the most frequently used measure of stroke impairment. 1,[5][6][7][8] This stroke-specific scale has been widely used in clinical trials to measure baseline severity or progress associated with investigational therapies. [5][6][7][8] A recent study by Muir et al 9 shows that baseline NIH Stroke Scale predicts 3-month outcomes (alive at home, alive in care, or dead).…”
mentioning
confidence: 99%
“…1,[5][6][7][8] This stroke-specific scale has been widely used in clinical trials to measure baseline severity or progress associated with investigational therapies. [5][6][7][8] A recent study by Muir et al 9 shows that baseline NIH Stroke Scale predicts 3-month outcomes (alive at home, alive in care, or dead). Individuals who scored greater than 13 on the NIH Stroke Scale had very poor functional outcomes (alive in care or death) compared with those who scored 13 or less.…”
mentioning
confidence: 99%